2007
DOI: 10.1063/1.2724772
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ferromagnetism in Co-doped La0.5Sr0.5TiO3−δ nanoparticles

Abstract: The authors report room temperature ferromagnetism in La0.5Sr0.5Ti0.985Co0.015O3−δ nanoparticles with particle sizes of ∼12–14nm. Nanoparticles of undoped and Co-doped samples were synthesized by a polymerized complex method and were characterized using x-ray diffraction and transmission electron microscopy. The magnetic properties of the nanoparticles were determined using vibrating sample magnetometry. The undoped samples exhibit a diamagnetic behavior, whereas all the Co-doped samples are ferromagnetic havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The saturated magnetization (Ms) increases as annealing temperature decreases, and attains the peak value (Ms =0.11 emu/g) at 973 K, then it decreases when the annealing temperature decreases. These phenomena have been observed in Co-LSTO [13]. But in Fe-LSTO particles [14], the Ms values increase monotonously with increase of annealing temperature.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…The saturated magnetization (Ms) increases as annealing temperature decreases, and attains the peak value (Ms =0.11 emu/g) at 973 K, then it decreases when the annealing temperature decreases. These phenomena have been observed in Co-LSTO [13]. But in Fe-LSTO particles [14], the Ms values increase monotonously with increase of annealing temperature.…”
Section: Resultsmentioning
confidence: 70%
“…Except Ni, the peaks of Ti, Sr, and La were observed. The Cu and C came from a copper grid and carbon contamination [13,14]. Our results indicate that using the sol-gel method, part of Ti ions was successfully substituted by Ni ions in the Ni-LSTO structure.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In a study of perovskite oxides with a general formula of La 0.4 Sr 0.6 Ti 1Àx Mn x O 3Àd (x = 0, 0.2, 0.4 and 0.6), Fu et al [3] reported that the materials were thermally and chemically compatible with yttria-stabilized zirconia and could be used as anodes in electrolyte-supported cells. In addition, Wongsaprom et al [4] demonstrated the existence of ferromagnetism in Co-La 0.5 Sr 0.5 TiO 3 and they indicated that the undoped samples were diamagnetic, whereas the Co-doped sample showed ferromagnetism at room temperature.…”
Section: Introductionmentioning
confidence: 96%